ANALISIS PENILAIAN HARGA SAHAM PERDANA DENGAN MENGGUNAKAN METODE FREE CASH FLOW TO THE FIRM ( Studi Kasus PT. Jakarta Propertindo ) - , Yadly Rozali ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The objective of this thesis is to analyze and calculate the intrinsic stock value of PT Jakarta Propertindo for determining fair stock price at Initial Public Offering (IPO). The method used in this thesis is top-down fundamental analysis which begin with macro economy analysis, followed by industry analysis and internal company analysis to predict the performance and prospect of the company in the future. The data used are companyâs financial statement from 2007â2011, macro-economic data and real estate/property indusry data. The result using free cashflow to the firm method suggests that the stock value of PT Jakarta Propertindo is Rp 1.823,11 per share.